P13 New HIV diagnoses in a busy inner-city cohort: How far have we come?. (23rd May 2012) - Haidari, G; Tsemunhu, P J; Mazhude, C; Dukoff-Gordon, A
Abstract : Background: Our service is located in a high HIV prevalence area (6.2/1000), and a large proportion of late presentations. We have widened the availability of HIV testing as a major strategy to reduce HIV related morbidity and mortality in our population. Aims/Objectives: To assess the evolving trends in demographics, clinical and laboratory findings of newly diagnosed HIV patients in our busy inner city clinic. To develop HIV testing strategies further with the implementation of current NICE guidance that recommends testing all medical admissions, and assess the potential future impact of this on presentation patterns in our cohort. Methods: Retrospective case note review of 92 consecutive new HIV diagnoses between 2009 and 2011. Data were collected on demographics, clinical stage, CD4 count, source of referrals, and drug resistance. Findings were compared to previous data sets in the same clinic over three audit periods between 2003 and 2011. Results: The proportion of males newly diagnosed has increased from 33% (2003) to 51% (2011), and the median age of all diagnoses has crept up to 39.5 years from 36.7 years. The proportion of referrals from primary care is now the largest (51%). Very late presenters (CD4 <200), remain high in our population at 53%, and this is well above the national average of 30%. Primary drug resistance is 16%, currently double the national average. Discussion/Conclusions: There continues to be a high rate of very late presenters in our cohort. Strengthening current interventions and implementation of NICE guidance will be essential in an effort to reduce late diagnoses.